Development of a flexible and conductive elastomeric composite based on chloroprene rubber. (February 2018) - Maya, M.G.; George, Soney C.; Jose, Thomasukutty; Kailas, Lekshmi; Thomas, Sabu
Abstract: Flexible and conductive nanocomposites with enhanced mechanical and dielectric properties have been fabricated from reduced graphene oxide (RGO) reinforced polychloroprene rubber (CR). Composites were prepared on a two-roll mixing mill and the morphological analysis using SEM and TEM showed good dispersibility and exfoliation of RGO layers in the matrix. It imparted a critical role in the enhancement of mechanical and electrical properties of the composites. Composites with 0.9 phr of RGO showed an enhancement in tensile strength, tensile modulus and electrical conductivity as 92%, 75%, and 103% respectively more than the pristine polychloroprene. RGO formed a good conducting percolating network in the polychloroprene matrix and it led to the formation of a dielectric composite material with enhanced electrical properties. Graphical abstract: Highlights: RGO reinforced Chloroprene rubber nanocomposite were prepared by mill mixing method. Exfoliation of graphitic layers leads to better interaction between RGO and CR. Overall improvement in mechanical and thermal properties. Morphological studies confirms the improvement in characteristic properties. 103% of improvement in electrical conductivity.